The EFEKTIVITAS KOMBINASI TERAPI AKUPUNTUR DAN REBUSAN TEH HIJAU DALAM MENURUNKAN KADAR GLUKOSA PADA PASIEN DIABETES TIPE 2 - anindini Winda Amalia (Universitas Citra Bangsa, 2019)
Diabetes mellitus type 2 is one of the major health problems in the world. Uncontrolled diabetes mellitus can cause serious complications such as kidney disease, visual impairments, cardiovascular disease and leg amputations that contribute to morbidity and mortality in diabetic patients. There are recommended additions to use and prevent diabetes and secondary complications, one of which is supplementation of a combination of acupuncture and decoction of green tea. The design of this study was quasi-experimental, a sample of 30 people divided into three groups, 10 people received acupuncture therapy, 10 people received decoction of green tea, and 10 people received combination of acupuncture and green tea. Interventions carried out for 4 weeks, with acupuncture therapy 2 times a week and drinking decoction of green tea twice a day. Data analysis to determine differences in each group using ANOVA test. The results of this study were obtained in the ANOVA test at week 2 with a p value of 0.016 and at week 4 with a p value of 0.002 (p <0.05) which means there were differences in glucose levels in patients with diabetes mellitus type 2 who were given a combination of acupuncture and decoction of green tea with only received acupuncture or decoction of green tea. Keywords: acupuncture, diabetes mellitus type 2, green tea, glucose levels